Formarsi nei luoghi dell'anima - Franco Cambi (Firenze University Press, 2016)
This article presents some observations about the role of the 'places of soul in education'; the personal and collective plaes, the natural places, the cultural and artistic places, the sacred place and the places of unconscious.